2021
DOI: 10.3390/bios11020043
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Enzyme-Based SPR Strategy for Detection of the Antimicrobial Agent Chlorophene

Abstract: Chlorophene is an important antimicrobial agent present in disinfectant products which has been related to health and environmental effects, and its detection has been limited to chromatographic techniques. Thus, there is a lack of research that attempts to develop new analytical tools, such as biosensors, that address the detection of this emerging pollutant. Therefore, a new biosensor for the direct detection of chlorophene in real water is presented, based on surface plasmon resonance (SPR) and using a lacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The samples from natural water were collected from a river located in León city, Guanajuato-México (21 • 09 54.0 N 101 • 43 30.6 W) according to the method presented by Quintanilla-Villanueva [17]. The water samples were spiked with chlorophene, following the recommendations of the surrogate addition method established by the IUPAC-AOAC [23].…”
Section: Samples and Hplc Reference Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The samples from natural water were collected from a river located in León city, Guanajuato-México (21 • 09 54.0 N 101 • 43 30.6 W) according to the method presented by Quintanilla-Villanueva [17]. The water samples were spiked with chlorophene, following the recommendations of the surrogate addition method established by the IUPAC-AOAC [23].…”
Section: Samples and Hplc Reference Methodsmentioning
confidence: 99%
“…The calibration curve followed the equation I (mV) = 8.9c + 3.4 [mg L −1 ] with a correlation coefficient of 0.994 (Figure 7c). However, the HPLC measurement carried out on real samples spiked These matrix effects can be attributed to the organic matter in the river sample, which reached a concentration of 23.66 mg L −1 [17]. It has been reported that organic matter can These matrix effects can be attributed to the organic matter in the river sample, which reached a concentration of 23.66 mg L −1 [17].…”
Section: Analysis Of Real Samplesmentioning
confidence: 99%
See 3 more Smart Citations